Improbable landing – the Sioux city miracle. Issue 2 (15th February 2022) - O'Brien, Jamie; Licht, John-Gabriel
Abstract : Research methodology: The technical reports released by the National Transportation Safety Board, along with secondary data in the form of available public data, such as news reports, interviews and memos, were used to round out the synopsis of the case study. Case overview/synopsis: This case explores the events that led up to the crash of United Airlines Flight 717 (for anonymity), in Sioux City, Iowa, on July 19, 1989, and the subsequent investigation. The case uses secondary sources to highlight the positive team interactions between the pilots that led to the crash landing not being as catastrophic as it might have been with 185 survivors in an extreme crisis scenario. The teaching note focuses on the importance of cognitive bias, psychological safety and teamwork in a crisis situation, and practical recommendations for managers at all levels. Complexity academic level: Organizational Behavior at the undergraduate and graduate level. Leadership and Change at the graduate and graduate level.